2013
DOI: 10.1111/dote.12077
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase D1 mRNA level may predict cancer-specific survival in heavy smokers with esophageal squamous cell cancers

Abstract: Protein kinase D1 (PRKD1) is a kinase that regulates various pathways, which involve in cell proliferation, apoptosis, cell adhesion and invasion. Although PRKD1 expression has been observed in many cancers, its role in esophageal squamous cell cancer (ESCC) has not been well reported. As its dysregulation in cancers is organ specific, we sought to investigate the potential role of PRKD1 in the progression of ESCC. Samples were collected from 178 patients with completely resected ESCCs at Sun Yat-sen Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Finally, we showed that PKD1 expression does not correlate with classical clinical and pathological prognostic factors (SBR histological grade, macroscopic tumour size, PR and ERBB2 statuses and PIK3CA mutation status). This interesting point suggests that PKD1 may also represent a novel attractive independent prognostic factor in breast cancer as recently described for esophageal squamous and laryngeal cancers.…”
Section: Discussionsupporting
confidence: 62%
“…Finally, we showed that PKD1 expression does not correlate with classical clinical and pathological prognostic factors (SBR histological grade, macroscopic tumour size, PR and ERBB2 statuses and PIK3CA mutation status). This interesting point suggests that PKD1 may also represent a novel attractive independent prognostic factor in breast cancer as recently described for esophageal squamous and laryngeal cancers.…”
Section: Discussionsupporting
confidence: 62%
“…This may provide an as yet unknown link between DDX3X and ARID1A , at least in terms of how promoter swapping may activate PRKD1 in these tumors. The PRKD1 gene encodes a kinase that has previously been implicated in colorectal, breast, esophageal, laryngeal, and other cancers, although deletion and/or gene silencing appear to be the mechanisms associated with colorectal and breast cancers (Borges et al, ; Brim et al, ), while activation is associated with esophageal and laryngeal cancers (Fountzilas et al, 2014; Xie et al, ). Along with the related PRKD2 and PRKD3 genes, it is associated with signal transduction in the diacylglycerol (DAG) and protein kinase C (PKC) pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Along with the related PRKD2 and PRKD3 genes, it is associated with signal transduction in the diacylglycerol (DAG) and protein kinase C (PKC) pathway. When activated PRKD family of kinases have a role in signal transduction, trafficking, migration, differentiation and proliferation (Xie et al, ) and potentially may serve as targets for future drug therapies. Further studies are required to elucidate the mechanism of PRKD gene activation in these tumors and how this leads to tumor proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, PRKD1 gene expression is increased in subpopulations of cancers of the colon, liver, and upper aero-digestive system, as revealed by searching COSMIC (catalog of somatic mutations in cancer). Recently, high PKD1 mRNA levels have been linked to lower cancer-specific survival in heavy smokers with esophageal squamous cell cancers (74) and predicts recurrence in laryngeal cancer (12). Indeed, the level of PRKD1 expression has been proposed as a laryngeal cancer prognostic marker for routine clinical applications.…”
Section: Discussionmentioning
confidence: 99%